2021
DOI: 10.1210/clinem/dgab691
|View full text |Cite
|
Sign up to set email alerts
|

Low-Iodine Diet of 4 Days Is Sufficient Preparation for 131I Therapy in Differentiated Thyroid Cancer Patients

Abstract: Context No consensus exists about the optimal duration of the low iodine diet (LID) in preparation of 131I therapy in differentiated thyroid cancer (DTC) patients. Objective This work aimed to investigate if a LID of four days is enough to achieve adequate iodine depletion in preparation for 131I therapy. In addition, the nutritional status of the LID was evaluated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…A second cornerstone of preparation for I-131 treatment generally consists of a low-iodine diet for a period of 1–2 weeks before administration; however, a recent study showed that a 4-day low-iodine diet seems to be sufficient in areas with iodine-sufficient intake ( 40 , 114 , 115 ). Although in use for many years, its effect on therapy outcome is not uniformly accepted; here, local iodine sufficiency status might also play a role.…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%
See 2 more Smart Citations
“…A second cornerstone of preparation for I-131 treatment generally consists of a low-iodine diet for a period of 1–2 weeks before administration; however, a recent study showed that a 4-day low-iodine diet seems to be sufficient in areas with iodine-sufficient intake ( 40 , 114 , 115 ). Although in use for many years, its effect on therapy outcome is not uniformly accepted; here, local iodine sufficiency status might also play a role.…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%
“…Although its merit is still subject to some scientific debate, a low-iodine diet before I-131 therapy may favorably influence the uptake of I-131 in DTC during therapy and will do no harm. Therefore, the expert panel agreed to recommend a low-iodine diet for at least 4 days before the administration of I-131 treatment ( 115 ).
Recommendation 16A: We recommend that TSH stimulation (>30 mI/L) is induced before I-131 therapy in order to facilitate I-131 uptake (4S).
…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…While the American Thyroid Association [8], British Thyroid Association [9], and Italian Society of Endocrinology [10] recommend 1-2 weeks, the 2022 European Thyroid Association supports a low-iodine diet but does not specify the duration [11]. South Korean researchers have advocated a strict low-iodine diet for 1 week before 131 I treatment [12,13], while a Dutch study suggested that a 4-day low-iodine diet may be su cient [14]. The Guidelines for Radioiodine Therapy of Differentiated Thyroid Cancer (2014 edition) propose 1-2 weeks, extended to 2-4 weeks in the 2021 edition [6], but these recommendations lack high-quality supporting evidence.…”
Section: Duration Of Low-iodine Dietmentioning
confidence: 99%
“…Adequate patient preparation for RAI [low-iodine diet and thyroid stimulating hormone (TSH) stimulation] is essential to ensure sufficient therapeutic uptake. A recent study shows that a low-iodine diet for 4 days provides equivalent thyroid stimulating hormone (TSH) stimulation to 7 days [42], which may improve patient compliance. RAI should also be delayed at least four weeks following computed tomography with iodinated contrast [43].…”
Section: Radioactive Iodine Imaging Therapy and Dosimetrymentioning
confidence: 99%